RUAYA BEBERAPA JENIS IKAN DI SUAKA PERIKANAN, SUNGAI LEMPUING, SUMATERA SELATAN - Susilo Adjie (Universitas Gadjah Mada, 2008)
The purpose of this research was to know the migration pattern of fishes in the fisheries reserved of Lempuing River. Research was conducted in fisheries reserved areas along Lempuing River system from April 1998 to March 1999. The fishes migration patterns werenamely catfish (Mystus nemurus), kissing gourami (Helostoma temmincki) and carp (Osteochillus hasselti). The results showed that around 3.80 % of 394 tagged fish were recaptured. Recapture fishes were dominated by catfish (M. nemurus) which have the farthest migration than other group. Habitat of fisheries reserved, especially cannals, must be obstacles free to facilitate the migration.